UKRAINIAN MASS MEDIA (1941–2009) ABOUT THE DESTRUCTION OF KHRESHCHATYK IN SEPTEMBER 1941 - Illia Afanasiev (Інтегровані комунікації, 2025)
In 2022–2025, numerous air attacks targeting Kyiv led to the deaths of many non-combatants in Kyiv and the destruction and damage of hundreds of civilian buildings. Against the backdrop of these hostilities, modern mass media publications dedicated to similar events of the past look more topical. Waves of interest in the topic of the destruction of Khreshchatyk in September 1941 rise every year in hundreds of Ukrainian mass media. Working with historical material requires a high level of journalistic qualification. However, such qualifications are lacking in Ukrainian journalism. The study aims to create a fact-checking tool for mass media reports about the destruction of the Kyiv city center (September 1941).